2016
DOI: 10.18632/oncotarget.13956
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of long noncoding RNAs in non-small cell lung cancer: a meta-analysis

Abstract: Non-small cell lung cancer (NSCLC) is the most common type of lung cancer. The overall 5-year survival rate of patients is extremely low and to find a new marker is urgently needed. Numerous studies indicate that long noncoding RNAs (lncRNAs) abnormally express in cancers. However, the results have been disputed, especially in the aspects of tumor prognosis. Therefore, we performed this meta-analysis to systematically summarize the relationship between lncRNAs expression and NSCLC. A total of 34 eligible studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…LncRNAs have also been demonstrated to gain various functions in tumorigenesis of lung cancer. However, most of the studies concerned the general NSCLC, but few focused on LUSC [ 19 ]. Thus, identification of LUSC-related lncRNAs, and investigation of their clinical roles and molecular mechanisms are essential for understanding the development and progression of LUSC.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs have also been demonstrated to gain various functions in tumorigenesis of lung cancer. However, most of the studies concerned the general NSCLC, but few focused on LUSC [ 19 ]. Thus, identification of LUSC-related lncRNAs, and investigation of their clinical roles and molecular mechanisms are essential for understanding the development and progression of LUSC.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, aberrant expression of multiple lncRNAs were found to be involved in the tumorigenesis and many of them were correlated with cancer prognosis [ 9 11 ]. Multiple lncRNAs have been reported to be promising prognostic indicators for cancers, such as hepatocellular carcinoma [ 12 ], non small cell lung cancer [ 13 , 14 ], osteosarcoma [ 15 ], ovarian carcinoma [ 16 ], and renal cell carcinoma [ 17 ]. So far, many studies have shown that lncRNAs also played critical roles in BC [ 18 ], these findings support that lncRNAs can be developed as novel potential prognostic biomarkers in patients with BC.…”
Section: Introductionmentioning
confidence: 99%
“…In spite the “junk” of genome lncRNAs being considered as insignificant, they are now confirmed to exert pivotal roles in tumor biological processes, including carcinogenic or antitumor effects via transcriptional and posttranscriptional regulations [ 6 , 7 ]. Furthermore, emerging evidence has indicated that the abnormal expression of lncRNAs was correlated with progression of neoplasms, including clinical-pathological features and prognostic outcomes [ 7 12 ]. Therefore, lncRNA can serve as a potential biomarker for predicting progression and survival in patients with carcinomas.…”
Section: Introductionmentioning
confidence: 99%